Meningkatkan Keterampilan Motorik Halus Menggunakan Media Kreatif (Origami) pada Anak dengan Autisme Kelas I SDLB - Rozak, Apriana; Saputra, Antoni; Marlina, Marlina; Budi, Setia; Zulpiani, Mardhatillah (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve fine motor skills in children with autism in grade I of SDLB (Special Needs Elementary School) through creative origami media. The study involved 3 students with autism in grade I of SDLB at SLBN 2 Kota Jambi. This research uses a Classroom Action Research (PTK) approach conducted in two cycles. Each cycle consists of the stages of planning, action implementation, observation, and reflection. The success indicators observed include hand-eye coordination, folding precision, finger strength, and students' independence in doing origami. The data were analyzed descriptively through tables and graphs per session. The research action subjects were grade 1 SDLB teachers teaching students with autism, and the impact subjects were 3 students with autism in grade 1 SDLB whose progress was measured. Data collection techniques were conducted through observation, interviews, and documentation. The indicators of success include improvements in teachers' skills in designing and implementing origami activities, as well as their impact on students' development and fine motor skills progress. The research results show a significant increase in fine motor skills, where the initial average score of 1 with the category 'Not Yet Able, Needs Full Assistance' increased to 3 with the category 'Able with Verbal/Sign Assistance' and up to 4 at the end of the cycle with the category 'Independent and Neat,' achieving ≥80% in all observed indicators.